Egressas do curso de Pedagogia UAB/UFSM: os desafios da iniciação na carreira docente - Simon, Beatriz de Araujo (2020)
This study investigates the challenges of beginning teachers, graduates of the Pedagogy course UAB / UFSM, when entering the teaching career. It is linked to the Postgraduate Program, Professional Master in Public Policies and Educational Management (PPPG), from Research Line 2 (LP2): Pedagogical Management and Educational Contexts, from the Research Group, Practices and training for teaching : basic and higher education (GPDOC). The general objective of the study is to understand what confrontations that the graduates of the EAD / UAB Pedagogy course face when entering the teaching career. As specific objectives it was outlined: to map the number of graduates of the UAB Pedagogy course at UFSM and their insertion in the teaching career; to identify confrontations experienced by the graduates of the Pedagogy course at UFSM in the beginning of the teaching career; infer indicators on the relationship between initial training and teacher confrontations; promote online training spaces to share the experiences of the graduates of the course. The investigation was developed based on a qualitative narrative approach of a socio-cultural nature (FREITAS, 2002), which was carried out through questionnaires, semi-structured interviews and the organization of online collaborative spaces. Supporting the study are Vaillant's studies; Marcelo (2012, 2018), Marcelo (1999) Cunha (2012), Huberman (2000), Imbernón (2009) Powaczuk (2008, 2012, 2017), Bolzan (2002, 2008) which makes it possible to promote listening, contextualization, experimentation and shared re-elaboration (ECER) about the challenges that beginners face when starting their teaching career. The research subjects are the graduates of the Pedagogy course UAB / UFSM in the years 2017, 2018 and 2020. The relationship of the author with the study is emphasized, in view of her insertion as a tutor in the Pedagogy Course in question, in particular in the disciplines related to supervised internships, which has allowed to follow the challenges of academics in the management of pedagogical work. The developed study allowed us to indicate the need to expand the processes aimed at beginners in the teaching career, enhancing the relationships between the initial and continuing education of teachers, as well as the interlocutions between academia and the context of professional performance. We show that starting from the teacher confrontations intended in the narratives and the development of indicators related to initial training, they need to be the focus of attention and training investment, because when inserted in practice, they are guided by a series of elements imbricated in the pedagogical practice and the search for continuity. training aims to contribute to the professional development of teachers. With this, online training spaces directed from Collaborative Networks to share experiences about initiation as a way to boost emancipatory processes of doing and feeling teaching are presented as a product resulting from this research, bringing training spaces closer to the times. times work spaces.